Enhancing ESL Learners' Speaking Proficiency through Adaptive ICALL Tools: A Mixed-Methods Study - Iftikhar, Sehrish; Binti Romly, Raihana; Akhter, Shamim; Hamisu Haruna, Hamisu; Akhtar Khan, Saleem; Aziz, Musharraf (Forum for Linguistic Studies, 2025)
Adaptive Intelligent Computer-Assisted Language Learning (ICALL) technologies are reshaping the development of speaking skills among ESL learners. The goal of the study is to investigate the impact of the ICALL adaptive system on learners' speaking proficiency. This study also depicts the learners' personal ICALL experiences. An in-depth analysis of contemporary literature is conducted to uncover the recent development and trends in ICALL for enhancing speaking skills. Concerning ICALL, the study also investigates the role of artificial intelligence (AI), natural language processing (NLP) and intelligent tutoring systems (ITS) in improving speaking skills. A mixed-methods sequential explanatory research design is employed. The quasi-experimental method is used for the first part. The 110 participants are divided into two groups as control and experimental group. The three ICALL applications MyET, Duolingo and ELSA are used to improve learners' speaking skills during the intervention. The intervention is only provided to the experimental group. The second part consists of semi-structured interviews. The seven participants who participated in the intervention were selected for interviews. Quantitative data are analyzed using SPSS and qualitative data are analyzed through thematic analysis following Grbich's approach. Findings reveal that ICALL tools contributed to notable gains in speaking accuracy and fluency after consistent use. ESL learners also reported increased confidence and expressed favorable perceptions regarding the ICALL tools' ease of use, instant feedback features and autonomous learning. Based on the posttest, which shows an 86.56% average improvement in speaking proficiency scores, it is strongly recommended that the ICALL tools be adopted as core approach to support speaking skills development.